Perspective: Ambient Air Pollution: Inflammatory Response and Effects on the Lung's Vasculature. (1st March 2014) - Grunig, Gabriele; Marsh, Leigh M.; Esmaeil, Nafiseh; Jackson, Katelin; Gordon, Terry; Reibman, Joan; Kwapiszewska, Grazyna; Park, Sung‐Hyun
Abstract : Particulates from air pollution are implicated in causing or exacerbating respiratory and systemic cardiovascular diseases and are thought to be among the leading causes of morbidity and mortality. However, the contribution of ambient particulate matter to diseases affecting the pulmonary circulation, the right heart, and especially pulmonary hypertension is much less documented. Our own work and that of other groups has demonstrated that prolonged exposure to antigens via the airways can cause severe pulmonary arterial remodeling. In addition, vascular changes have been well documented in a typical disease of the airways, asthma. These experimental and clinical findings link responses in the airways with responses in the lung's vasculature. It follows that particulate air pollution could cause, or exacerbate, diseases in the pulmonary circulation and associated pulmonary hypertension. This perspective details the literature for support of this concept. Data regarding the health effects of particulate matter from air pollution on the lung's vasculature, with emphasis on the lung's inflammatory responses to particulate matter deposition and pulmonary hypertension, are discussed. A deeper understanding of the health implications of exposure to ambient particulate matter will improve our knowledge of how to improve the management of lung diseases, including diseases of the pulmonary circulation. As man‐made ambient particulate air pollution is typically linked to economic growth, a better understanding of the health effects of exposure to particulate air pollution is expected to integrate the global goal of achieving healthy living for all.